KARAKTERISTIK INDIVIDU, KARAKTERISTIK PEKERJAAN DAN KARAKTERISTIK ORGANISASI PENGARUHNYA TERHADAP KEPUASAN KERJA PEGAWAI - Kamela, Ice (Jurnal Benefita, 2016)
The paradigm of public sector management has been shifted from new public management (NPM) to public value management (PVM).  Public value management focused on how to build the relationship with the society as constituent of government. Therefore, every aspect of the management, including human resources management, has to be revisited, such as job satisfaction. Thus, this study aim to investigate the relationship between Individual,  Job  and organization characteristic on Job Satisfaction in public sector organization. By using 38 respondents working in the Dinas Pariwisata Ekonomi Kreatif Pemuda dan Olahraga Kaupaten Pesisir Selatan. The hypoteses test  used quantitative analyssys mhetods through  of multiple linear regrassion.The find that individual  and job characteristic has a positive significant relationship with job satisfaction.  While Organization characteristic has not significant with job satisfaction. In addition, this finding indicate that two-factor theory partially can explain this phenomena. Therefore, the evidence from this study suggest that organization has to improve individual and job characteristics in order to get the higher job satisfaction among employees.  tion, this finding indicate that haracteristic has a positive significant relationship with job ssatisfcation.  sektor le (h Keyword :  individual characteristics, job characteristics, organizational characteristic  job satisfaction.